Sugarcane Labor Migration in Brazil - Jones, Terry-Ann. author. aut Link
XI, 116 p. 5 illus. in color.
Keywords: ‘The history of capital is the history of labour exploitation. In this beautifully written monograph, Terry-Ann Jones traces that history in a single country – Brazil – by following the vicissitudes of seasonal, domestic workers who are exposed to the most cruel extremes of capital accumulation. As second-class citizens of their own country, internal migrant sugar cane workers in Brazil today exhibit all the deep scars of their precursors in this historically unforgiving industry: poverty, powerlessness, displacement, marginalization and human desperation.’—Anton L. Allahar, Professor of Sociology, Western University, Canada “Sugar Cane Labor Migration in Brazil provides a rich ethnohistorical analysis of one crucial story of contemporary labor relations that is always gendered and raced: the neo-slavery conditions that structure sugar cane production in Brazil. She interviewed migrant sugar cane workers and observed their work and living conditions for 10 years, gaining access to dramatic accounts of how they struggled to survive economic hardship, deplorable housing, poor nutrition, and systemic criminalization. This book sheds necessary light on the colonial legacies of racial capitalism and the direct relationship between labor, national belonging, and access to citizenship rights and resources.” —Keisha-Khan Y. Perry, PhD, Associate Professor of Africana Studies, Director of Graduate Studies, Brown University, USA This book examines the experiences of seasonal, migrant sugarcane workers in Brazil, analyzing the deep-seated inequalities pervasive in contemporary Brazil. Education, employment, income, health, and relative political power are forefront in this study of the living and working conditions of the transient population. Based on ten years of qualitative research dominated by in-depth interviews with migrant sugarcane workers, this projectargues that the ills of the sugarcane industry are symptomatic of an overarching problem of unequal access to opportunities by all Brazilian citizens. The project is unique in its use of a single industry as an expression of the multifarious problems of socioeconomic, regional, and racial inequality. The author explores details of the labor migration experience with a central premise that the conditions are not a direct outcome of the industry, but rather a manifestation of fundamental inequalities rooted in Brazil’s colonial history. Terry-Ann Jones is Associate Professor of Sociology & Anthropology at Fairfield University, USA. She studies international and domestic migration between and within Latin America, the Caribbean, North America, and Africa. She is currently researching the roots of xenophobia in South Africa.